2015
DOI: 10.7236/ijasc.2015.4.1.145
|View full text |Cite
|
Sign up to set email alerts
|

Friction Stir Welding Tool Geometries Affecting Tensile Strength of AA6063-T1 Aluminum Alloy Butt Joint

Abstract: Friction Stir Welding (FSW) is a solid state welding that could successfully weld the difficult-to-weld-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…The results indicated that the friction-stir-welding tool geometry considerably influences the material flow in the nugget zone and, consequently, the weld mechanical properties. 26 The influence of the pin geometry on various properties of friction-stir-welded samples made with tools with different pin profiles was proved. In the case of four-flute cylindrical-pin profiles, friction-stir welding could not be performed on an aluminium alloy.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the friction-stir-welding tool geometry considerably influences the material flow in the nugget zone and, consequently, the weld mechanical properties. 26 The influence of the pin geometry on various properties of friction-stir-welded samples made with tools with different pin profiles was proved. In the case of four-flute cylindrical-pin profiles, friction-stir welding could not be performed on an aluminium alloy.…”
Section: Introductionmentioning
confidence: 99%
“…The FSW process is used to weld a 6.3 mm thickness of AA6063 -T1 aluminum alloy butt joint. The mechanical properties such as a tensile strength and a hardness of the joint were examined and compared with the microstructure of the joint [6]. The optimum welding condition for the friction stir welding (FSW) process applied to AHSS was considered.…”
Section: Introductionmentioning
confidence: 99%